The use of artificial intelligence in numerical learning of geometry for students with mild intellectual disabilities - Wulandari, Dini; Istadi, Istadi; Muttaqien, Anwar (Universitas Muhammadiyah Yogyakarta, 2024)
Education is very important nowadays. Education plays an important role in improving human resources. Children are asked to be able to understand various sciences well, one of which is geometry in mathematics lessons. However, there are still many children who have difficulty getting a decent education, especially children with intellectual disabilities. This article aims to review effective learning methods for students with intellectual disabilities in understanding geometric material and being able to apply it in solving problems in real life contexts. One branch of mathematics that needs to be studied in depth is geometry. Since childhood, we have started to recognize objects that actually use geometric shapes. These objects are even simple objects that we often encounter around us. Apart from knowing the shapes and formulas in geometry, we are also expected to be able to apply geometry in everyday life. Students with intellectual disabilities are expected to have numerical abilities in solving geometry problems. This research uses a qualitative descriptive method by describing and analyzing data related to the discussion. Students with intellectual disabilities need learning media that can be more interactive and can increase understanding and creativity in thinking. By using artificial intelligence teachers can develop more effective learning media for students.